2001
DOI: 10.4141/a97-060
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and the addition of white clover improves the nutritional quality of orchardgrass cultivars

Abstract: . 2001. Grazing and the addition of white clover improves the nutritional quality of orchardgrass cultivars. Can. J. Anim. Sci. 81: 597-600. Two experiments were conducted to determine the nutritional quality of orchardgrass (OG) cultivars under hay and rotational grazing systems during the first 2 production years. Crude protein content was higher and fibre content lower in OG managed as rotationally grazed pasture compared with that harvested as hay. The K:Ca + Mg ratio was reduced and Cu deficiency was amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Results of a pan-European experiment, which included a Canadian site, have demonstrated that mixing grasses and legumes increases dry matter (DM) yield (Finn et al 2013) with no negative effects on nutritive value (Sturludóttir et al 2013). Adding a legume into a grass sward has been shown to increase forage DM yield and crude protein concentration (Barnett and Posler 1983) and improve forage nutritive value (Papadopoulos et al 2001). Furthermore, mixing timothy (Phleum pratense L.) with alfalfa (Medicago sativa L.) has been shown to increase the non-structural carbohydrate concentration of forages (Bélanger et al 2014), potentially resulting in a more efficient use of nitrogen (N) by ruminants (Brito et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Results of a pan-European experiment, which included a Canadian site, have demonstrated that mixing grasses and legumes increases dry matter (DM) yield (Finn et al 2013) with no negative effects on nutritive value (Sturludóttir et al 2013). Adding a legume into a grass sward has been shown to increase forage DM yield and crude protein concentration (Barnett and Posler 1983) and improve forage nutritive value (Papadopoulos et al 2001). Furthermore, mixing timothy (Phleum pratense L.) with alfalfa (Medicago sativa L.) has been shown to increase the non-structural carbohydrate concentration of forages (Bélanger et al 2014), potentially resulting in a more efficient use of nitrogen (N) by ruminants (Brito et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…), particularly white clover (WC). Legumes such as WC are valued for their N‐fixing ability (Chestnutt et al, 1980) and tendency to increase forage quantity and quality (Sleugh et al, 2000; Papadopoulos et al, 2001), as well as increase N availability for neighboring grasses during decomposition of legume roots (Ledgard and Steele, 1992; Paynel et al, 2001). White clover can contribute as much as 545 kg ha –1 of N to pasture swards (Elgersma and Hassink, 1997) and is therefore a valued forage species for livestock producers.…”
mentioning
confidence: 99%
“…Incorporating a legume into a grass sward has been shown to increase yield and crude protein (Barnett and Posler 1983), and improve forage nutrient value (Papadopoulos et al 2001). Because perennial legumes generally have a greater proportion of deeper roots, soil space is used more efficiently and direct competition with grasses is reduced (Buxton and Wedin 1970).…”
mentioning
confidence: 99%